The Effect of Photoperiod to Break Dormancy of Porang’s (Amorphophallus muelleri Blume) Tuber and Growth - Serafinah Indriyani; Wahyu Widoretno (Research Journal of Life Science, 2016)
The aim of the research was to obtain the method of porang’s tuber dormancy breaking. The source of porang’s tuber were obtained from Rejosari Village, Bantur Subdistrict, Malang Regency. The diameter and weight of porang’s tuber were 5-7 cm and 100-150 g respectively. The research design was Completely Randomized Design. Porang’s tubers were storaged in the photoperiod cabinet during one month. The levels of photoperiod were 0, 8, 12, 16, 20, and 24 hours/day. The light intensity of TL lamp was 400 lux. As a control it was used porang’s tuber that it was placed in the dark cabinet without light.  Repetition was four times. The success of dormancy breaking was observed through the tuber capasity to grow that it was identified by bud  emerged. Data were analyzed by ANOVA that it was continued by Duncan test (α = 0.05). The results showed that photoperiod 8, 12, 16, 20, and 24 hours/day during one month could stimulate porang’s tuber dormancy breaking. Photoperiod 16 hours/day emerged the height of buds 4.97 ± 1.20 mm and the diameter of buds 7.28 ± 1.22 mm at photoperiod 24 hours/day. The growth of porang’s tuber which is treated by photoperiod during one month were significantly different with control. Photoperiod 16 hours/day emerged the height of plants and the diameter of petiole were 106.38 ± 15.11 cm and 2.90 ± 0.29 mm respectively, while the width of canopy was 72.50 ± 22.17 cm at photoperiod 24 hours/day.  Besides, the diameter and weight of harvest tuber were 7.93 ± 2.20 cm and 383.20 ± 23.58 g. The weight of harvest tuber increased 255% from the early weight of tuber. Photoperiod treatment promote breaking of porang’s tuber dormancy.